1999
DOI: 10.1002/(sici)1099-0690(199907)1999:7<1745::aid-ejoc1745>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

New Water-Soluble Diamine Complexes as Catalysts for the Hydrogenation of Ketones Under Hydrogen Pressure

Abstract: New water‐soluble rhodium and iridium complexes of 2,2′‐bipyridines, functionalized with PO3Na2 groups, show very good catalytic activities in the reduction of various substituted acetophenones under hydrogen pressure in basic aqueous media. No significant loss of catalyst activity is observed after one use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
(1 reference statement)
1
24
0
Order By: Relevance
“…Recently, Töllner et al reported on the solution and monolayer hydrogenation of acetone to 2-propanol by the complex (4,4‘-dialkyl-2,2‘-bipyridine)rhodium(hexadiene) hexafluorophosphate (alkyl = methyl or heptadecyl). The solution reactivity of similar complexes was earlier reported by Mestroni et al, and more recently by, for example, Pénicaud et al In an acetone solution (alkyl = methyl), the complex shows a low activity of 500 turnover numbers (TON) after 48 h and little selectivity between acetone and butanone. When, however, a monolayer, specifically a Langmuir−Blodgett film, is prepared from the complex (alkyl = heptadecyl), the reactivity changes dramatically, and in an aqueous acetone solution over 50 000 TON are obtained in 48 h. Moreover, the catalyst becomes selective to acetone and does not reduce butanone at all.…”
Section: Introductionsupporting
confidence: 77%
“…Recently, Töllner et al reported on the solution and monolayer hydrogenation of acetone to 2-propanol by the complex (4,4‘-dialkyl-2,2‘-bipyridine)rhodium(hexadiene) hexafluorophosphate (alkyl = methyl or heptadecyl). The solution reactivity of similar complexes was earlier reported by Mestroni et al, and more recently by, for example, Pénicaud et al In an acetone solution (alkyl = methyl), the complex shows a low activity of 500 turnover numbers (TON) after 48 h and little selectivity between acetone and butanone. When, however, a monolayer, specifically a Langmuir−Blodgett film, is prepared from the complex (alkyl = heptadecyl), the reactivity changes dramatically, and in an aqueous acetone solution over 50 000 TON are obtained in 48 h. Moreover, the catalyst becomes selective to acetone and does not reduce butanone at all.…”
Section: Introductionsupporting
confidence: 77%
“…Based on the commonly accepted mechanism together with observations made in the literature by Bujoli et al [59] and Zhang et al [61] (see Scheme 6), the main role of the added base appears to be deprotonation of the intermediate A, while water can protonate the alkoxide ligand. A is obtained from the insertion of a ketone into one of the M-H bonds.…”
Section: Resultsmentioning
confidence: 93%
“…The suspension was stirred at room temperature for another 24 2.4. General procedure for hydrogenation [59] In a Schlenk tube 0.06 mmol of ligand (1, 2) and 0.96 ml of 1 M aqueous sodium hydroxide solution was added to 10 ml of water under argon and the mixture was degassed. After complete dissolution of the ligand, 0.03 mmol of metal precursor (Rh (III) acetate, [RuCl 2 (p-cymene)] 2 ) was added.…”
Section: Synthesis Of 1-methyl-3 (Butyl-4-sulfonate) Benzimidazolium mentioning
confidence: 99%
“…This procedure is an adaptation of a reduction protocol employed for the synthesis of 4-(diethoxyphosphoryl)aniline [26].…”
Section: Synthesis Of 4-(diethoxyphosphorylmethyl)anilinementioning
confidence: 99%